Performance, Bone Parameters and Phosphorus Excretion of Broilers Fed Low Phosphorus Diets Supplemented with Phytase from 23 to 40 Days of Age - El-Sherbiny, A.E.; Hassan, H. M.A.; Abd-Elsamee, M.O.; Samy , A.; Mohamed, M.A.S. (International Journal of Poultry Science, 2010)
An experiment was conducted using 300 growing Ross 308 broilers from 23 to 40 days of age. Six dietary treatments were formulated. A basal diet contained 1.48% Dicalcium Phosphate (DCP) was used as a control diet (diet 1). Diets 2 and 3 contained 50% and 25% of the DCP of diet 1 (0.74 and 0.37%, respectively), while diet 4 was formulated without DCP. Diets 3 and 4 were fed without or with supplemented phytase enzyme (500 U/kg). Every dietary treatment was fed to 5 replicates (10 chicks each). The results showed no significant differences between birds fed diets containing 1.48 % DCP or 0.74% DCP on BWG, FI and FCR. Reducing dietary DCP level to 0.37% slightly decreased BWG compared with birds fed 0.74% DCP with inferior value of FCR. When DCP was removed from the diet BWG significantly (p<0.01) decreased and FCR recorded worth value. Addition of 500 U phytase/kg to diet 3 of 0.37% DCP significantly enhanced BWG (p<0.01), feed intake and FCR (p<0.05). Addition of phytase to the diet of no DCP did improve neither BWG nor FCR. Decreasing dietary DCP did not significantly affect length, weights and width of tibia either with or without phytase supplementation. However, birds fed the highest level of dietary DCP showed the highest values of tibia weight and length among the different groups. Tibia breaking strength (kgf) significantly (p<0.001) decreased as dietary DCP level decreased. Addition of phytase significantly (p<0.001) improved tibia breaking strength and tibia ash %. Addition of phytase to diet of low DCP did increase tibia Ca and P to reach values comparable with those of the control diet. Decreasing dietary DCP showed significant (p<0.001) decrease in the excreted Ca and P. Addition of phytase to diets of low or no DCP also decreased (p<0.001) the excreted Ca and P. This means that phytase increased the utilization of dietary Ca and P. The excreted Ca and P decreased by 41.22% and 55.26%, respectively, when birds were fed diet of no DCP compared to those fed the control diet. Also, addition of phytase enzyme to diets of low or no DCP decreased the excreted percentage of Ca and P. It could be concluded that reducing dietary P level and using phytase enzyme could be used to limit quantity of P excreted from broilers. This reduce such impact in environmental pollution.